Impact of Globalisation on Religious Tourism: The Case of Vrindavan, India - Gupta, Charlie (The international journal of religious tourism and pilgrimage, 2024)
The term ‘religious tourism’ refers to travel that is primarily inspired by spiritual beliefs (Smith, 2012). It serves as one of humanity’s oldest religious practices as well as one of the earliest examples of tourism (Timothy, 2011). Due in the main to the numerous sacred places that are dispersed throughout its vast geographic area, India, which is known for its rich heritage and culture, has attracted attention from throughout the world (Eck, 2011; Singh, 2013). As a result, it has become a well-known location for religious tourism. During the past ten years, this specific type of tourism has seen a tremendous increase in growth rates, leading to considerable changes at important spiritual and religious places. Intense globalisation and rapid urbanisation have been prompted by the influx of tourists and pilgrims, profoundly altering the terrain (Harris, Griffin & Williams, 2002). This paper delves into this phenomenon through a case study of Vrindavan, a significant city situated on the banks of the Yamuna River in northern India, which has held great religious significance and serves as a prominent pilgrimage destination (Shinde, 2011). However, as part of a larger process of globalisation and ensuing urbanisation, and the entry of numerous transnational chains starting in the 1960s, there have been significant changes. The idea of a pilgrimage to Vrindavan has changed, moving away from its original meaning as a trek to the home of the gods and instead becoming more of a holiday and leisure destination. This change has produced exciting opportunities for investors and developers, prompting growing urbanisation and a notable break from the customary pilgrimage practices that were traditionally observed. The study examines the ways in which globalisation influences the establishment of new sacred places supported by various faith-based organisations by using a case study approach and a purposive survey method (Kothari, 2004). Considering the concomitant processes of religious commercialisation and spatial transformation, the article seeks to shed light on the consequent impact on the spiritual experience and the larger pilgrimage patterns throughout the city. The study ends by making suggestions for steps that can be taken to lessen the effect of globalisation on a city’s spiritual essence and make sure that urban growth is in harmony with its history and sacred values.